Detection of Hepatic Problem in Dogs and Cats by Biochemical Assay and Imaging Technique (X-Ray and Ultrasonography) (Global Journal of Medical Research, 2021)
Keeping pet (dogs and cats) has become a cultural phenomenon throughout the world including Bangladesh. Hepatic problem is an important health issue that may cause mortality of these pet. This study was conducted with the aimed to detect the hepatic problem in dogs and cats along with its frequency in different sex, age and breeds of animals. A total of 100 clinically suspected animals (50 dogs and 50 cats) were included in the study. After thorough clinical examination, 2 ml bloods were collected by venue puncture in serum vials for biochemical analysis. After that all animals were subjected to x-ray and ultrasonography. In biochemical analysis standard deviation of hepatic enzymes (902.48 u/l ALP, 626.66 u/l ALT, 722.98 u/l AST in dog and 564.22 u/l ALP, 300.06 u/l ALT, 340.00 u/l AST in cat) and bilirubin (2.02 mg/dl in dog and 5.22 mg/dl in cat) were remarkably above the mean value (333.86±127.63 u/l ALP, 256.36±88.62 u/l ALT, 261.62±102.24 u/l AST, bilirubin 0.72±0.29 mg/dl in dog and 245.42±79.79 u/l ALP, 180.16±42.43 u/l ALT, 188.99±48.08 u/l AST, 1.81±0.74 mg/dl bilirubin in cat).
Keywords: serum biochemistry; x-ray; ultrasonography; hepatic problem; dogs and cats